THE DEVELOPMENT OF ENGLISH CHILDREN’S LITERATURE (Eureka Journal of Language, Culture & Social Change, 2026)
English children’s literature has developed through a long historical process shaped by changing social values, educational theories, and cultural transformations. This article examines its evolution from early didactic and religious texts to modern imaginative and global literary works. It highlights key stages, major authors, thematic shifts, and the growing recognition of childhood as an independent cultural and psychological category. The study shows that children’s literature in England has moved from moral instruction toward creativity, emotional depth, and social diversity, reflecting broader developments in society and literary culture.
Keywords: Children’s literature, English literature, childhood, fantasy fiction, moral education, Victorian era, narrative development, literary evolution, Roald Dahl, J. K. Rowling.